Langues, identités et expériences de la diversité - Valentin Feussi (Recherches en didactique des langues et des cultures)
This article purports to examine the relevance of a reception approach to the notion of "francophonies". Unlike the institutional, technical and descriptive points of view which favor the semiotic dimensions for a diffusionist conception of languages, the reception option starts from the meaning projected in a given situation for the person(s) involved (including the researcher). This meaning very often emerges via contact with the surrounding world, based on reference points which are not necessarily material, sometimes sensitive, and which only historialization makes possible to explain. The experiences of vernacularization in language urbanity contexts in Cameroon are an illustration of this. They show the relevance of the construction of meaning for oneself in one’s relations to otherness, thanks to identity mobility in Francophone sociolinguistic dynamics. We can thus infer that promoting the stance of an appropriation of French or a reception approach to francophonie amounts to considering French as it is, with no desire to explain it, but that of understanding it. This way, French resonates with the way people live, without a diffusionist background whose ethical consequences could harm the dynamics of this language.